Death, Belief and Politics in Central African History - Kalusa, Walima Tuesday, 1964-; Vaughan, Megan (Book collections on Project MUSE., 2014)
In this set of essays Walima T. Kalusa and Megan Vaughan explore themes in the history of death in Zambia and Malawi from the late nineteenth century to the present day. Drawing on extensive archival and oral historical research they examine the impact of Christianity on spiritual beliefs, the racialised politics of death on the colonial Copperbelt, the transformation of burial practices, the histories of suicide and of maternal mortality, and the political life of the corpse.